If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x = 6x + -15 Reorder the terms: 2x = -15 + 6x Solving 2x = -15 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 2x + -6x = -15 + 6x + -6x Combine like terms: 2x + -6x = -4x -4x = -15 + 6x + -6x Combine like terms: 6x + -6x = 0 -4x = -15 + 0 -4x = -15 Divide each side by '-4'. x = 3.75 Simplifying x = 3.75
| 5m+8+4(3m-3)-3(m+3)=0 | | ln(2x+3)=2 | | -(6x-5)-(4x-5)+13=-11(x-1)-(4x+11)+3 | | 1.5y+2x=20 | | 4+9x+x=20x-35 | | -85-9x=104-30x | | 3(a-4)=7z+4 | | 4m+8+5(4m-5)-5(m+5)=0 | | x^2-(2a-1)x+a^2-a+1=0 | | 0.57x^3+4x=4 | | 70x+90y=350 | | 0.2(p+6)-0.7(p+4)=-3 | | 0.57x^3+4u=4 | | 6y+12-4=-10 | | 4b^2+b-19=0 | | 3x+4(2x-3)=6 | | 2(f-9)=-24 | | 4=x^4 | | 3+2y-24=14 | | 7+3x=7x-29 | | 45=x-36 | | 6c-1=23 | | 216=5x | | -3(2t+3)=-3 | | -133=-7(6n+7) | | -2x+3(3x-6)=-2-9x | | 10(s-4)=-85 | | 2m-8=10+18 | | 3x+1y=392 | | 14x-9=11y | | 900000000000000000000000000000000+423523542546224624246426264462264264642426264426565374676585798966975685362431432134245436356457764575976980=x | | k-3(5)=12(5) |